Sport facility operations management : a global perspective - Schwarz, Eric C.; Hall, Stacey A. ;Shibli, Simon (New York : Routledge, 2020)
This is a comprehensive and engaging textbook introducing cutting-edge concepts and best practice in sport facility operations management. Each chapter contains real-world case studies and discussion questions, innovative 'Technology Now' and new 'Facility Focus' features, and 'In the Field' segments about what is going on in the industry. This new edition also provides new content in the areas of project management, social and digital media, revenue generation and diversification, performance analytics, and impacts and legacies.
1 Introduction to sport facility operations management -- SECTION I Pre-management and pre-operational issues -- SECTION II Application of management and operations principles for sport facilities -- SECTION III Implementing sport facility operations management -- SECTION IV Effectiveness of management and operations -- Index.
Includes bibliographical references and index.
Keywords: SPORTS FACILITIES -- MANAGEMENT